Serum Zinc Levels in Children and Adolescents With Type-1 Diabetes Mellitus - Z Karamizadeh; M Jalali; R Majdzadeh; MR Eshraghian; A Djazayery; M Estakhri; M Chamari; M Peyrovi Milani (Tehran University of Medical Sciences, 2011)
Background: There have been very few studies, with contradictory results, on the zinc status of children and adolescents with type-1 diabetes mellitus. The objective of this cross-sectional study was to determine zinc status based on the serum zinc concentration in type-1 diabetic children and adolescents and compare it with that of healthy controls.Methods: Thirty children and adolescents with type-1 diabetes mellitus, aged 6 to 18 years, and 30 age- and sex-matched healthy controls participated in the study. Serum zinc, fasting blood sugar, hemoglobin A1c and serum albumin were measured by flame atomic absorption spectrophotometry, enzymatic colorimetry, ion-exchange chromatography and colorimetry using bromocresol green methods, respectively.Results: No statistically significant difference was found in the mean serum zinc concentration between diabetic patients and healthy controls (111.0 ± 3.1 and 107.1 ± 3.8 mg/dl respectively, P= 0.4). No correlations were found between the serum zinc levels and fasting blood sugar, hemoglobin A1c, or the duration of the disease in the patients.Conclusion: The zinc levels of diabetic children and adolescents are not noticeably different compared to those of healthy controls and are independent of glycemic control and the duration of the disease.